Anaerobic test in four free swimming techniques through inertial sensors - Chirico, E.; Tessitore, A.; Vannozzi, G.; Demarie, S. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Water sports performance optimisation relies on specific, reliable procedures to assess physiological and biomechanical improvement, useful for coaches to monitor the athlete`s conditions and predict future performance. [1,2,3]. A new approach to swimming coaching has been offered by innovative wearable technologies and waterproof coatings. They provide not only reliable and objective analysis of stroke mechanics and race performance, but also of physiological qualities such as the anaerobic capacity, all directly in free swimming [5]. The present study aimed to assess if a free-swimming protocol with inertial sensors may provide an effective assessment of kinematic and functional capacity in swimmers, specialized in four different techniques, by measuring speed and stroke parameters and their correlation with race time.